2015
DOI: 10.1152/ajprenal.00564.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pendrin gene ablation alters ENaC subcellular distribution and open probability

Abstract: The present study explored whether the intercalated cell Cl−/HCO3− exchanger pendrin modulates epithelial Na+ channel (ENaC) function by changing channel open probability and/or channel density. To do so, we measured ENaC subunit subcellular distribution by immunohistochemistry, single channel recordings in split open cortical collecting ducts (CCDs), as well as transepithelial voltage and Na+ absorption in CCDs from aldosterone-treated wild-type and pendrin-null mice. Because pendrin gene ablation reduced 70-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 43 publications
0
61
2
Order By: Relevance
“…Perfusion-fixed mouse kidneys were labeled immunocytochemically (36) or immunohistochemically (37) using the following antibodies: c-Kit (Cell Signaling Technology, Cat. # 3074), V-ATPase A-subunit (36), EPS8 (Santa Cruz, sc-390257), Fosb (Santa Cruz, sc-398595), Foxpl (Santa Cruz, sc-398811), Hoxd8 (Santa Cruz, sc-515357), Scin (Santa Cruz, sc-376136), Tfap2b (Santa Cruz, sc-390119), AE4 (38), pendrin (37), AQP2 (Knepper laboratory, K5007).…”
Section: Methodsmentioning
confidence: 99%
“…Perfusion-fixed mouse kidneys were labeled immunocytochemically (36) or immunohistochemically (37) using the following antibodies: c-Kit (Cell Signaling Technology, Cat. # 3074), V-ATPase A-subunit (36), EPS8 (Santa Cruz, sc-390257), Fosb (Santa Cruz, sc-398595), Foxpl (Santa Cruz, sc-398811), Hoxd8 (Santa Cruz, sc-515357), Scin (Santa Cruz, sc-376136), Tfap2b (Santa Cruz, sc-390119), AE4 (38), pendrin (37), AQP2 (Knepper laboratory, K5007).…”
Section: Methodsmentioning
confidence: 99%
“…The existence of such cross-talk was expected given that in vitro, variations in extracellular pH or Cldirectly affect ENaC activity (11,12), suggesting that changes in acid/base transporter activity in intercalated cells can impact ENaC-mediated Na + reabsorption. Indeed, studies in WT and pendrin-null mice have demonstrated that both the cell surface expression and the open probability of ENaC are upregulated by pendrin (32,59). Pendrin modulates ENaC abundance and activity by, at least in part, increasing the luminal concentration of HCO 3 and/or pH (57); the underlying molecular mechanisms have yet to be determined.…”
Section: Interactions Between Principal Cells and Type B Cellsmentioning
confidence: 99%
“…Ϫ exchange, because this cell type is found primarily in the CNT of the mouse kidney (86) and because mouse CNT is very difficult to perfuse in vitro, CNT transport properties are not well understood. Principal cells mediate the absorption of Na ϩ primarily through the epithelial Na ϩ channel, ENaC (53). However, in the CCD and most probably in the CNT as well, significant Cl Ϫ absorption occurs through transcellular transport across type B and non-A, non-B intercalated cells (64), such as through apical electroneutral Na ϩ -independent, Cl Ϫ /HCO 3 Ϫ exchange (31,63,86,87).…”
Section: Intercalated Cell Subtypes and Their Role In Acid-base Regulmentioning
confidence: 99%
“…In particular, Na ϩ /H ϩ exchanger isoform 3 (NHE3), ␣1-Na-K-ATPase, Na ϩ -K ϩ -2Cl Ϫ cotransporter (NKCC2), ENaC, and NCC abundance was similar in lysates from wild-type and Slc26a4 null mice following a balanced, NaCl-replete diet (32). However, following dietary NaCl restriction or with an aldosterone infusion, pendrin gene ablation reduces ␣-, ␤and ␥-ENaC subunit abundance in the kidney (32,50,53). In particular, pendrin gene ablation blunts the aldosterone-induced increment in 70-kDa ␥-ENaC abundance.…”
Section: Pendrin Modulates the Aldosterone-induced Increment In Enac mentioning
confidence: 99%
See 1 more Smart Citation